Mulheres egressas da Educação de Jovens e Adultos na universidade: uma análise na perspectiva da relação com o saber - Santiago, Nilda Gonçalves Vieira (2020)
The present research had as general objective to understand and analyze how the academic trajectory and the relationship with knowledge at the university were constituted, by students graduating from Youth and Adult Education. The analysis of the life and school trajectories of these students was proposed, in which the knowledge constituting the identity formation, the academic strategies developed and the mobilization for entering and staying at the university were observed. The challenges and difficulties experienced by them during the course were also analyzed, from the process of access to higher education, through permanence or not until academic success. It was also sought to understand the meanings that the knowledge produced by the university acquire for these women and contribute to a better conception of the aspects of the school trajectory of women from the popular strata, which makes it an indication of paths that allow to re-signify studies and policies. The object of this study consists of three elements, namely: the nature of the university, the social origin of the graduates of EJA and the problem of the relationship with knowledge. This is a case study carried out with eight graduates of Youth and Adult Education, students of the Pedagogy and History courses at UEG - Campus Goianesia. The methodological choice was qualitative research, having as basic sources of data the in-depth interviews conducted with students who were in the following situations at the university: frequent (who are at least in the second year of the course), away / avoided and who have already completed the course. This methodology aimed to ensure a more plural data collection for the interpretative analysis of personal and school trajectories. Bibliographic material was also collected, data was collected at the academic secretariat of the Campus, analysis of the socioeconomic questionnaire of the freshmen and analysis of documents from the University, such as PDI (Institutional Development Plan), Pedagogical Projects of undergraduate courses, among others. others, in order to support the understanding of the object in its entirety. As a theoretical contribution, to conduct the study, we mainly used the theory of the relationship with Bernard Charlot's knowledge and Paulo Freire's conceptions about the human being as a being of relationships. This work was also based on the school trajectories of students from the lower classes, in the studies of Nadir Zago and Bernard Lahire. Regarding the discussion about the university, the reflections made came from thoughts such as Ildeu Moreira Coêlho and Marilena Chauí. In the data analysis, the following analysis categories emerged: 1) Perceptions about EJA as a motivation for higher education; 2) Strategies and movements for entering and staying at the university; 3) The relationship with university knowledge. The three categories were articulated and showed the meanings and motivations of the university course experienced by the women surveyed. The study showed that the trajectories experienced by these women are unique stories, although the importance of the social determinant of the stratification of Youth and Adult Education is recognized. The way they appropriated knowledge and the academic context, even if limited by the precarious conditions of the institution, is specific to each one and happens through the relationship established with themselves and with others. The work also revealed that the relationship with the knowledge that the majority constituted at the university was linked to the prospects for a better life, personal and professional growth and not necessarily to reflection, creation and freedom of thought, as expected from those who enter the university space.